FAKTOR RISIKO KEJADIAN BALITA DENGAN BERAT BADAN DI BAWAH GARIS MERAH (BGM) DI DESA PANCAROBA KECAMATAN AMBAWANG KABUPATEN KUBU RAYA TAHUN 2015 - Alamsyah, Dedi; Rohmady, Roby (JUMANTIK (Jurnal Mahasiswa dan Peneliti Kesehatan), 2016)
Weight Under the Red Line (BGM) ie when the weight of the baby or toddler is under the red line on the KMS (Card Towards Healthy). Based on secondary data obtained in the village Pancaroba 8 toddlers below the red lines of the existing total of 211 children (instead of D / S). From the above data it is known that there are parents who have parenting poor nutrition and poor knowledge               The aim in this study was to determine the "Risk Factors Genesis Toddler With Weight Under the Red Line (BGM) Pancaroba In the village of Kubu Raya Subdistrict Ambawang.The study design was an observational study with an analytical approach or cross-sectional study design. Total sampling in this study is a mother who has children as much as 39 people. Data collection techniques and instruments are primary and secondary data. The data analysis technique used is the analysis of univariate and bivariate. Data collected by interview using a questionnaire.               The result is that the risk factors associated with the Red Line Toddlers (BGM) is ASI ekskusif with P value = 0.026 (PR = 0.114) and access to health care utilization by P value = 0.020 (PR = 5.75). Keywords: Exclusive Asi, access Yankes, BGM